Factors Influencing Youth Interest in Agriculture in Karangan Village - Jumini Sri Wahyuni; Sujarwo Sujarwo; Asihing Kustanti (Eduvest - Journal of Universal Studies, 2024)
The role of youth in agricultural development is very important, but youth who are interested in agriculture tend to decrease every year. Youth in Karangan Village consider farming to be an unprofitable profession. They consider the economics of agricultural products to be very low so that most of them are not interested in agricultural activities. Therefore, the number of farmers decreases every year. So efforts to increase the interest of the younger generation to be involved in the agriculture sector. Motivational factors are needed to encourage someone to want to do something, and the motivational factor in question is interest. There are several factors that determine a person’s interest. This research aims to analyze the factors that influence youth interest in agriculture. This research was conducted on youth from Karangan Village, Kepohbaru District, Bojonegoro Regency, with 88 respondents from a total population of 785. Observation and questionnaires are techniques used by researchers to collect data. This research is quantitative research with data analysis using the SEM PLS method. This research uses 3 independent variables, namely individual characteristics (age, education, family), external factors (training and counseling, availability of natural resources, government support), and motivational factors (rewards, achievement, life demands) on the dependent variable, namely youth interest (enjoyment, involvement, interest). Factors that influence youth interest based on the result of the analysis are age, family, availability of natural resources, life demands and involvement.